Problem indywidualizmu w Stanisława Brzozowskiego filozofii czynu - Brzozowski, Tomasz Tadeusz (Folia Philosophica, 2018)
During Brzozowski’s lifetime, individualism, taken as philosophical standpoint, was one of typical theoretical tools. After the “standing on the edge of a precipice” period in 1901—1903 he was struggling with the cultural crisis, in this time a common experience, hence, the activity of the agent taken as an individual, showed up as a way beyond contemplation, opening the possibility of individual and unlimited acting, which could transform the passive subject into a real creator. Brzozowski’s individualism includes axiological and cultural relativization, which enabled him to link different aspects of Nietzsche’s, Kant’s and Fichte’s theories. This syncretism remained open to some logical difficulties, however, with which Brzozowski struggled to the end of his work. With a critique of naturalism, which he found to be scientific justification of relativism, he drew upon Kant and Fichte and formulated anew the primal standpoint of radical individualism by granting a value-creative character to subjective human thought. This way the individual self makes the world behind it the space of consolidating values.